International variations in the gestational age distribution of births: an ecological study in 34 high-income countries. (8th September 2017) - Delnord, Marie; Mortensen, Laust; Hindori-Mohangoo, Ashna D; Blondel, Béatrice; Gissler, Mika; Kramer, Michael R; Richards, Jennifer L; Deb-Rinker, Paromita; Rouleau, Jocelyn; Morisaki, Naho; Nassar, Natasha; Bolumar, Francisco; et al.
Abstract: Background: Few studies have investigated international variations in the gestational age (GA) distribution of births. While preterm births (22–36 weeks GA) and early term births (37–38 weeks) are at greater risk of adverse health outcomes compared to full term births (39–40 weeks), it is not known if countries with high preterm birth rates also have high early term birth rates. We examined rate associations between preterm and early term births and mean term GA by mode of delivery onset. Methods: We used routine aggregate data on the GA distribution of singleton live births from up to 34 high-income countries/regions in 1996, 2000, 2004, 2008 and 2010 to study preterm and early term births overall and by spontaneous or indicated onset. Pearson correlation coefficients were adjusted for clustering in time trend analyses. Results: Preterm and early term births ranged from 4.1% to 8.2% (median 5.5%) and 15.6% to 30.8% (median 22.2%) of live births in 2010, respectively. Countries with higher preterm birth rates in 2004–2010 had higher early term birth rates ( r > 0.50, P < 0.01) and changes over time were strongly correlated overall (adjusted- r = 0.55, P < 0.01) and by mode of onset. Conclusion: Positive associations between preterm and early term birth rates suggest that common risk factors could underpin shifts in the GA distribution. Targeting modifiable population risk factors for delivery before 39 weeks GA may provide a useful preterm birth prevention paradigm.